Growth Response, Production and Analysis of Revenue of Hiyung Cayenne Pepper (Capsicum frustescens L) with Dosage Application of Liquid Bokashi Fertilizar (LBF) from Cattle Wate and Rice Straw - Mahdiati Mahdiati; Danang Biyatmoko (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2020)
This study aimed to (1) analyze the nutrient content of liquid bokashi fertilizer (LBF) derived from cattle waste and rice straw, (2) analyze the effect of liquid bokashi fertilizer dose on plant height, age of first flowering, and the number of fruits in the first harvest, the weight of the first fruit, and the weight of fresh fruit biomass. Analyzing revenue (income versus cost) and the feasibility of planting the Hiyung cayenne pepper by applying LBF at various dosage levels. The method used in this study was a Single Complete Randomized Design (CRD) with data analysis using ANOVA with further testing of Real Differences (LSD). B0 was control (without bokashi). B1 consisted of 125 ml of LBF and water to dilute the solution up to 500 ml. B2 consisted of 250 ml of LBF and water to dilute the solution up to 500 ml. B3 consisted of 375 ml of LBF and 125 ml of water. B4 consisted of 500 ml of LBF. The results showed that the highest growth response (69 cm) occurred with the addition of 125 ml of LBF, while the lowest growth occurred in the control (B0). In the first age, the most optimal flowering occurs in the B2 of 60.00 dap, and lowest in the control (B0) of 50.00 dap. The highest number of fruits was obtained from B2 of 170.00 g, and the lowest was in B0 (control) of 94.00 g. The average weight of the first fruit was found in B2 of 285.00 g, and the lowest in B0 (control) of 126.00 g. The highest weight of plant biomass was found in B2 of 405.00 g, and the lowest was in B0 (control) of 177.75 g. The highest revenue analysis and business feasibility were found in B2, namely Rp. 17.065,00 and the ratio of 4,96. The lowest revenue occurred in Control, which was Rp 5.318,75, with a TR/TC value of 2,28. Based on the revenue analysis, B2 treatment produced the highest revenue and was the most feasible to be applied compared to other treatments.